Estudio socio-económico de los sistemas de producción alrededor del cultivo de Chocho en la parroquia Eloy Alfaro casó: Chan en la provincia de Cotopaxi 2017-2018. - Carrillo Carranza, Adrián Ricardo (2018)
The present project was carried out to carry out a socio-economic study of production around the cultivation of cunt in the Eloy Alfaro Parish case: Chan at Province of Cotopaxi. The proposed objectives were: to design and apply a survey with agro-socioeconomic indicators to the production systems around the cultivation of chocho in neighborhood Chan, analyze the obtained information on the social field , economic and productive level of the Production Systems around the chocho crop and socialize the obtained results at the diagnosis in the Chan. The types of research used at this project is the non-experimental and bibliographic documentary, the methods used were descriptive method and hypothetical deductive method; the survey was used as a study technique; Some diagnostic criteria for the elaboration of the surveys were: general characteristics of UPA, long-cycle crops, long-cycle crop pests, orchard, perception of pests, animals, labor. The surveys were applied 20 families in the neighborhood. With this research project, information was obtained with the sarandón theory that uses the multicriteria analysis to evaluate the sustainability of the agricultural farms, as a result of the social component it was 0.75, found in a sustainable average range (0.50-1) since it was obtained as results that the number of members per family farmers is 3 people per household, at economic field it resulted in 0.45 in an unsustainable range (lower 0.49-0) since the members of the neighborhood migrate to have sources of money in other activities and thus solve the economy of their families and in the component of production 0.56 was obtained that is sustainable (0.50-1) since their crops present economic losses to cause pest attack, as well as the use of a tractor for soil preparation.